Morphological features of the structure of liver complexes - Fazlitdin Khusniddinovich Olimkhuzhayev (Peerian Journals Publishing, 2022)
In an experiment on 226 white male outbred rats from birth to 8 months of age, different periods of postnatal ontogenesis were studied. We found that the initial link of blood outflow from the hepatic lobules are the initial hepatic venules, which are formed from the fusion of sinusoids in the subcapsular zone of the liver. From 2 weeks of age to the end of postnatal ontogenesis, liver revealed constantly occurring hepatic complexes. In postnatal ontogenesis, the main process is the formation of new structural and functional units in the subcapsular zone of the liver.
Keywords: Liver; ontogenesis; lobule; sinusoidal vessels